2020
DOI: 10.1016/j.chembiol.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Nonapoptotic Cell Death Using Chemical Biology Approaches

Abstract: Nonapoptotic cell death is important for human health and disease. Here, we show how various tools and techniques drawn from the chemical biology field have played a central role in the discovery and characterization of nonapoptotic cell death pathways. Focusing on the example of ferroptosis, we describe how phenotypic screening, chemoproteomics, chemical genetic analysis, and other methods enabled the elucidation of this pathway. Synthetic small-molecule inducers and inhibitors of ferroptosis identified in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 97 publications
0
17
0
Order By: Relevance
“…While the activities of the P47 and S47 isoforms are comparable in many respects, we find that human and mouse cells with the S47 variant show enhanced resistance to ferroptosis (19,21,24). Ferroptosis is a nonapoptotic programmed cell death process characterized by the accumulation of lethal lipid peroxides (25)(26)(27)(28). This oxidative process is implicated in several human pathologies and contributes to p53's role in tumor suppression and normal cell stress responses (19,21,29,30).…”
mentioning
confidence: 76%
“…While the activities of the P47 and S47 isoforms are comparable in many respects, we find that human and mouse cells with the S47 variant show enhanced resistance to ferroptosis (19,21,24). Ferroptosis is a nonapoptotic programmed cell death process characterized by the accumulation of lethal lipid peroxides (25)(26)(27)(28). This oxidative process is implicated in several human pathologies and contributes to p53's role in tumor suppression and normal cell stress responses (19,21,29,30).…”
mentioning
confidence: 76%
“…It has become evident that ferroptosis is a druggable pathway where ferroptosis inducers may be used to kill malignant cells, and ferroptosis inhibitors may be used to prevent cell and tissue loss in degenerative disorders. The full scope of pharmaceutical targets for ferroptosis and GPX4 have been summarized intensively in several recent reviews [117,119,124] Withaferin A Acts as a GPX4 inhibitor likely through its electrophilic groups [117] 265237…”
Section: Modulation Of Gpx4 To Probe Ferroptosismentioning
confidence: 99%
“…Inhibits system Xc likely by inhibiting one of its kinase targets. May induce necrotic cell death at high concentrations [99] 23672308 Diaryl-isoxazole Non-competitive System Xc-inhibitor [117,124] n.a Engineered human cyst(e)inase Systemic Depletion of Cysteine [117,124] n.a Tac-beclin1 System Xc-inhibitor [117,124] n.a Lanperisone (FDA-approved drug)…”
Section: Glutamatementioning
confidence: 99%
“…Ferroptosis is triggered through two mechanisms, either through the depletion of the cellular antioxidant glutathione (GSH), or through direct inhibition of the enzyme responsible for reversing lipid oxidation, glutathione peroxidase 4 (GPX4). While more detailed reviews of ferroptosis can be found elsewhere [ 3 , 6 , 7 ], here, we highlight the key compounds used in the elucidation of the mechanisms of ferroptosis. The first chemical agent found to trigger ferroptosis, Erastin, was originally identified in a high-throughput chemical library screen to identify compounds that were selectively lethal in oncogenic mutant HRAS V12 cells [ 8 ].…”
Section: The Development Of Ferroptosis Inducersmentioning
confidence: 99%